1998
DOI: 10.1103/physreve.57.6685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elongation on the phase behavior of the Gay-Berne fluid

Abstract: In this paper we present a computer simulation study of the phase behavior of the Gay-Berne liquid crystal model, concentrating on the effects of varying the molecular elongation . We study a range of length-to-width parameters 3рр4, using a variety of molecular dynamics and Monte Carlo techniques, obtaining a guide to the phase behavior for each shape studied. We observe vapor (V), isotropic liquid (I), nematic (N), smectic-A (S A ) and smectic-B (S B ) liquid crystal phases. Within the small range of elongat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 33 publications
10
135
1
1
Order By: Relevance
“…In our parametrization, the temperature of Tϭ400 K corresponds to the reduced temperature T*ϭk B T/⑀ 0 GB ϭ0.984, and we found that the state points appear to be in very good agreement with the results of Ref. 17 where the phase diagrams for GB potentials with adjacent values of ϭ3.4 and ϭ3.6 have been studied. The LCDr ͑as prepared in Sec.…”
Section: B Dendrimer In An Lc Solventsupporting
confidence: 76%
See 1 more Smart Citation
“…In our parametrization, the temperature of Tϭ400 K corresponds to the reduced temperature T*ϭk B T/⑀ 0 GB ϭ0.984, and we found that the state points appear to be in very good agreement with the results of Ref. 17 where the phase diagrams for GB potentials with adjacent values of ϭ3.4 and ϭ3.6 have been studied. The LCDr ͑as prepared in Sec.…”
Section: B Dendrimer In An Lc Solventsupporting
confidence: 76%
“…16͒ were used, which are appropriate for a united atom hydrocarbon model, and the cutoff distance for the potential was set to r c,1 ϭ9.8 Å (ϵ2.5 LJ ). For the GB sites we use the cut and shifted form of the potential studied by Brown and co-workers, 17 employing a length/breadth ratio ϭ3.5 and a side-to-side/end-to-end well depth ratio of Јϭ5. To scale to real units, values of GB ϭ3.829 Å ͑estimated from the dimensions of the mesogenic unit͒ and ⑀ GB /k B ϭ406.15 K ͑from Ref.…”
Section: A Liquid Crystalline Dendrimermentioning
confidence: 99%
“…As noted by Allen et al, 16 on cooling the SmB phase to very low temperatures no transition to a crystal could be identified and the SmB exhibited well-defined correlations characteristic of crystalline packing. Further evidence of the crystalline nature of the SmB phase was obtained after the calculation of the shear elastic modulus by Brown et al 17 On the basis of all this evidence, it was suggested that the reported SmB phase for the GB model was in fact crystalline and that it might be more appropriate to refer to this phase as a solid.…”
Section: Introductionmentioning
confidence: 89%
“…6,9,12 Simulations using different combinations of parameters have shown that the GB model exhibits an additional phase identified as smectic A ͑SmA͒. [15][16][17][18] All these simulation studies suggest that the occurrence of the SmB is not very sensitive to the particular parameterization, whereas the formation of the SmA phase requires the molecular elongation be large enough.…”
Section: Introductionmentioning
confidence: 99%
“…Gay and Berne originally suggested to choose the exponents µ = 2 and ν = 1. The phase behavior for this set of exponents has been studied in detail [27,28,29,30,31,32], for various choices of κ and κ ′ [30,31,32]. An example is shown in Figure 3.…”
Section: Gay-berne Particlesmentioning
confidence: 99%